A plant‐specific in vitro ubiquitination analysis system. (14th March 2013) - Zhao, Qingzhen; Tian, Miaomiao; Li, Qingliang; Cui, Feng; Liu, Lijing; Yin, Bojiao; Xie, Qi
Summary Protein ubiquitination requires the concerted action of three enzymes: ubiquitin‐activating enzyme (E1), ubiquitin‐conjugating enzyme (E2) and ubiquitin ligase (E3). These ubiquitination enzymes belong to an abundant protein family that is encoded in all eukaryotic genomes. Describing their biochemical characteristics is an important part of their functional analysis. It has been recognized that various E2/E3 specificities exist, and that detection of E3 ubiquitination activity in vitro may depend on the recruitment of E2s. Here, we describe the development of an in vitro ubiquitination system based on proteins encoded by genes from Arabidopsis. It includes most varieties of Arabidopsis E2 proteins, which are tested with several RING‐finger type E3 ligases. This system permits determination of E3 activity in combination with most of the E2 sub‐groups that have been identified in the Arabidopsis genome. At the same time, E2/E3 specificities have also been explored. The components used in this system are all from plants, particularly Arabidopsis, making it very suitable for ubiquitination assays of plant proteins. Some E2 proteins that are not easily expressed in Escherichia coli were transiently expressed and purified from plants before use in ubiquitination assays. This system is also adaptable to proteins of species other than plants. In this system, we also analyzed two mutated forms of ubiquitin, K48R and K63R, to detect various types of ubiquitin conjugation.